Influence of Different MRI Protocols on FGT Measurements. (7th April 2016) - Wengert, Georg J.; Pinker‐Domenig, Katja; Helbich, Thomas H.; Vogl, Wolf‐Dieter; Clauser, Paola; Bickel, Hubert; Marino, Maria‐Adele; Magometschnigg, Heinrich F.; Baltzer, Pascal A.
Abstract : The aim of this study was to investigate the influence of fat–water separation and spatial resolution in MRI on the results of automated quantitative measurements of fibroglandular breast tissue (FGT). Ten healthy volunteers (age range, 28–71 years; mean, 39.9 years) were included in this Institutional Review Board‐approved prospective study. All measurements were performed on a 1.5‐T scanner (Siemens, AvantoFit) using an 18‐channel breast coil. The protocols included isotropic (Di) [TR/TE1 /TE2  = 6.00 ms/2.45 ms/2.67 ms; flip angle, 6.0°; 256 slices; matrix, 360 × 360; 1 mm isotropic; field of view, 360°; acquisition time (TA) = 3 min 38 s] and anisotropic (Da) (TR/TE1 /TE2  = 10.00 ms/2.39 ms/4.77 ms; flip angle, 24.9°; 80 slices; matrix 360 × 360; voxel size, 0.7 × 0.7 × 2.0 mm 3 ; field of view, 360°; TA = 1 min 25 s) T 1 three‐dimensional (3D) fast low‐angle shot (FLASH) Dixon sequences, and a T 1 3D FLASH sequence with the same resolution ( T 1 ) without (TR/TE = 11.00 ms/4.76 ms; flip angle, 25.0°; 80 slices; matrix, 360 × 360; voxel size, 0.7 × 0.7 × 2.0 mm 3 ; field of view, 360°; TA = 50 s) and with (TR/TE = 29.00 ms/4.76 ms; flip angle, 25.0°; 80 slices; matrix, 360 × 360; voxel size, 0.7 × 0.7 × 2.0 mm 3 ; field of view, 360°; TA = 2 min 35 s) fat saturation. Repeating volunteer measurements after 20 min and repositioning were used to assess reproducibility. An automated and quantitative volumetric breast density measurement system was used for FGT calculation. FGT with Di, Da and T 1 measured 4.6–63.0% (mean, 30.6%), 3.2–65.3% (mean, 32.5%) and 1.7–66.5% (mean, 33.7%), respectively. The highest correlation between different MRI sequences was found with the Di and Da sequences ( R 2  = 0.976). Coefficients of variation (CVs) for FGT calculation were higher in T 1 (CV = 21.5%) compared with Dixon (Di, CV = 5.1%; Da, CV = 4.2%) sequences. Dixon‐type sequences worked well for FGT measurements, even at lower resolution, whereas the conventional T 1 ‐weighted sequence was more sensitive to decreasing resolution. The Dixon fat–water separation technique showed superior repeatability of FGT measurements compared with conventional sequences. A standard dynamic protocol using Dixon fat–water separation is best suited for combined diagnostic purposes and prognostic measurements of FGT. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Automated quantitative MRI measurement approaches of breast fibroglandular tissue (FGT), using different T 1 ‐ and T 2 ‐weighted sequences, as well as fat–water separation techniques, are introduced. This article investigates the influence of fat–water separation and spatial resolution in MRI on the results of automated quantitative measurements of FGT. Dixon fat–water separation techniques showed superior repeatability of FGT measurements compared with conventional sequences. A standard dynamic protocol using Dixon fat saturation is best suited for combined diagnostic purposes and prognostic measurements of FGT.